2020
DOI: 10.3390/nu12051444
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effects of Vitamin D in Thyroid Diseases

Abstract: Vitamin D is a secosteroid with a pleiotropic role in multiple physiological processes. Besides the well-known activity on bone homeostasis, recent studies suggested a peculiar role of vitamin D in different non-skeletal pathways, including a key role in the modulation of immune responses. Recent evidences demonstrated that vitamin D acts on innate and adaptative immunity and seems to exert an immunomodulating action on autoimmune diseases and cancers. Several studies demonstrated a relationship between vitami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 169 publications
2
28
0
7
Order By: Relevance
“…AITD has a multifactorial etiology, influenced by genetic factors (e.g., polymorphisms of TSH-R, Tg, human leukocyte antigens, and other genes associated with the immune response) [24], environmental factors (e.g., radiation, iodine, smoking habits, infections, selenium, drugs, stress, and dietary habits) [21,24,25], and endogenous factors (e.g., body mass index, adipokines, estrogens, selective X chromosome inactivation, microquimerism, glucocorticoids [21], and potentially the gastrointestinal microbiome) [26][27][28]. Given the immunomodulatory role of VitD, its relationship with AITD has been extensively studied in recent years [29].…”
Section: Vitamin D and Autoimmune Thyroid Diseasementioning
confidence: 99%
“…AITD has a multifactorial etiology, influenced by genetic factors (e.g., polymorphisms of TSH-R, Tg, human leukocyte antigens, and other genes associated with the immune response) [24], environmental factors (e.g., radiation, iodine, smoking habits, infections, selenium, drugs, stress, and dietary habits) [21,24,25], and endogenous factors (e.g., body mass index, adipokines, estrogens, selective X chromosome inactivation, microquimerism, glucocorticoids [21], and potentially the gastrointestinal microbiome) [26][27][28]. Given the immunomodulatory role of VitD, its relationship with AITD has been extensively studied in recent years [29].…”
Section: Vitamin D and Autoimmune Thyroid Diseasementioning
confidence: 99%
“…що дозволили суттєво змінити погляд на фізіологічну роль цього вітаміну [5][6][7]. Відкриття рецепторів до гормонально-активних форм вітаміну D і їх синтезу в нетрадиційних для цього вітаміну клітинах різних органів і тканин передбачає більш широкий спектр його фізіологічного ефекту [8].…”
Section: дефіцит вітаміну D та автоімунні захворювання щитоподібної зunclassified
“…Lately, studies have suggested that low vitamin D concentrations and other conditions which may result in reduced vitamin D function (e.g., certain Vitamin D receptor gene polymorphisms, pathologies of vitamin D gene and its binding protein) may increase the risk of AITDs [43,44]. Vitamin D is known to regulate the adaptive immunity and its deficiency has been linked to the development of Hashimoto's thyroiditis, Graves' disease, rheumatoid arthritis and systemic lupus erythematosus [45][46][47].…”
Section: Environmental Factorsmentioning
confidence: 99%